Perancangan Visual Identity Babsatu Coffee & Bakery di Payakumbuh - Muhammad Hazri Zein; Budiwirman Budiwirman (Universitas Negeri Padang, 2021)
Babsatu Coffee & Bakery is a coffee shop located in Payakumbuh City owned by Ikhsan Marza. This cafe does not yet have a logo, so the logo is designed in the form of a colored logo and typography to represent the previous concept so that consumers and potential customers can easily remember it. The logo was formed based on the concept of Gestalt similarity logo theory or similarity in shape by using the shape of an owl as a topping, a cup as an owl's body and coasters as legs, followed by the letters of the name